Expropriation with Hukou Change: Evidence from a Quasi-Natural Experiment - Mehtap Akgüç; Xingfei Liu; Massimiliano Tani (Institute for the Study of Labor (IZA), 2014)
We study the labor market outcomes of males aged 18-60 obtaining an urban hukou as a result of land expropriation across a number of provinces in China. Using 2008 and 2009 RUMiC data pooling urban, rural and migrant samples, we find that those obtaining an urban hukou have better labour market outcomes than rural stayers and migrants, and close the gap vis-à-vis native urbanites. We also find that children of families experiencing a hukou change due to expropriation have similar investment in human capital as the children of native urban hukou holders. The results confirm the hukou status as a strong economic determinant of labor market outcomes and as a source of inequality. Differences in educational investment, regardless of the differences in parental background, appear however to disappear for the children of families experiencing expropriation, suggesting that leveling the hukou status amongst children in an urban area may be a first step towards reducing intergenerational inequality.
Keywords: D19; H13; J18; O12; O43; R20; 330; expropriation; China; labour markets; economic reform; quasi-experiment